The Influence of Emotional Material on Encoding and Retrieving Intentions: An ERP Study in Younger and Older Adults - Hering, Alexandra; Kliegel, Matthias; Bisiacchi, Patrizia S.; Cona, Giorgia (Frontiers in Psychology, 2018)
Prospective memory is a cognitive process that comprises the encoding and maintenance of an intention until the appropriate moment of its retrieval. It is of highly relevance for an independent everyday life, especially in older adults; however, there is ample evidence that prospective memory declines with increasing age. Because most studies have used neutral stimuli, it is still an open question how emotional factors influence age-related differences in prospective remembering. The aim of the study was to investigate the influence of emotional material on prospective memory encoding, monitoring, maintaining, and retrieval in younger and older adults using behavioral and electrophysiological measures. We tested 24 younger adults (M = 26.4 years) and 20 older adults (M = 68.1 years) using a picture one-back task as ongoing activity with an embedded prospective memory instruction. The experimental task consisted of three sessions. In each session, participants had to encode series of images that represented the prospective memory cues for the consecutive block. The images were either of pleasant, unpleasant, or neutral valence. The pictures used in the ongoing task were likewise of pleasant, unpleasant, or neutral valence. Event-related potentials (ERPs) were recorded to assess the neural correlates of intention encoding, maintenance and self-initiated retrieval. We did not find age differences between younger and older adults on the behavioral level. However, the ERP results revealed an interesting pattern that suggested for both age groups elevated attentional processing of emotional cues during encoding indicated by an elevated LPP for the emotional cues. Additionally, younger adults showed increased activity for unpleasant cues. During the maintenance phase, both age groups engaged in strategic monitoring especially for pleasant cues, which led to enhanced sustained positivity. During retrieval, older adults showed increased activity of ERP components related to cue detection and retrieval mainly for pleasant cues indicating enhanced relevance for those cues. In conclusion, emotional material may influence prospective remembering in older adults differently than in younger adults by supporting a mixture of top-down and bottom-up controlled processing. The results demonstrated a negativity bias in younger adults and a positivity bias in older adults.